Frequency and Nature of Transfusion Related Adverse Reactions in Patients Admitted in A Tertiary Care Hospital (Bangladesh Journal of Medicine, 2021)
Background:Transfusion of blood and blood products if employed safely, with intensive care can save manyvaluable lives. But a number of transfusion reactions may develop that are sometimesmore serious and life threatening.So this study was done to find out the most frequent and life threatening reactions that develop during transfusion.Methods: A Cross sectional descriptive observational study was performed at a tertiary care centre. Patients of 18 years and older irrespective of sexes who received blood and blood products due to different reasons between April 2020 to September 2020 were included in this study. A total of 96 patients were included in the study.Results:In thisstudy 11(11.5%) out of 96 patients had transfusion reactions of different types .Febrile non haemolytic reaction was the highest with 8 patients (8.33%),followed by Allergic reaction in 2 patients(2.08%) and Acute haemolytic transfusion reaction in 1 patient (1.04%).Among them 7(63.6%) reactions occurred with whole blood , 2(18.2%) reactions occurred with red cell concentrate and 1 reaction occurred with Apheresis platelet (9.1%) and fresh frozen plasma(9.1%).Statistically significant association was found between duration of storage of blood and transfusion reaction.Conclusion: Febrile non haemolytic reaction was the commonest type of transfusion reaction found in this study and there was also statistically significant association between duration of storage of blood and transfusion reaction.Bangladesh J Medicine July 2022; 33(1) : 27-33